Task Sequencing for Students With Emotional and Behavioral Disorders: A Systematic Review. (January 2015) - Knowles, Christen; Meng, Paul; Machalicek, Wendy
We reviewed studies utilizing task sequencing to improve academic outcomes for children with emotional and/or behavioral disorders (EBD) in educational settings. Task sequencing interventions included high-probability, high-preference, and task interspersal interventions. Although task sequencing is commonly used in research, a synthesis of recent applications in educational settings for students with EBD is absent. Systematic searches of electronic databases and ancestral references identified 11 studies meeting inclusion criteria. These 11 studies were reviewed and analyzed for (a) participant characteristics, (b) experimental design, (c) type of academic outcome as the dependent variable, (d) intervention description, (e) certainty of evidence and research quality, and (f) reported student academic outcomes. Implications for continued applied practice and future research are discussed.